Study on the implementation of the European Physical Activity Guidelines Final Progress Report of Tender EAC-2014-0574 - Gelius, Peter; Rütten, Alfred; Goodwin, Lee; Marin, Mayra; Abu-Omar, Karim; Kahlmeier, Sonja; Martin-Diener, Eva; Murphy, Marie H.; Ferguson, Kyle; Cavill, Nick; Foster, Charlie (2016)
This report covers the activities and deliverables of a Tender issued by the European Commission, Directorate-General Education and Culture (DG EAC) to support the implementation of the European Physical Activity Guidelines in the year of 2015. The Tender group supported the EU Physical Activity Focal Point Network in the collection of data for the Monitoring Framework of the EU “Council Recommendation on promoting health-enhancing physical activity across sectors”. Specifically, the group provided revisions and reviews of the Staff Working Document (SWD) that accompanies the Monitoring Framework, supported the EU and WHO in developing a questionnaire, provided Focal Points with a series of webinars and ongoing support via phone and e-mail, and conducted an in-depth situation analysis in six of the Member States. Based on these activities, the group made recommendations to the European Commission for future improvements of the Monitoring Framework, the questionnaire, the SWD, and the support provided to Member States.
Keywords: Eu Tender